The effect of health education through peer group education on increasing adolescent knowledge about stunting - Lubis, Mutia Sari; Simamora, Asnil Adli; Batubara, Rini Amalia (Institute of Computer Science (IOCS), 2024)
Adolescents are a potential age group that can be involved in various stunting prevention programs from an early age. A young woman as a prospective mother has poor nutritional status, so she will be at risk of giving birth to children who have poor nutritional status, including stunting. Health education through peer group education is a very important and urgent intervention to increase adolescent knowledge about stunting. To determine the effect of health education through peer group education on increasing knowledge of young women about stunting. The research design was quasi-experimental using a one group pretest - posttest design. A sample of 60 students at SMA Negeri 1 Padangsidimpuan school used purposive sampling technique, then determined respondents according to the inclusion criteria. The results of the paired t test obtained the value of sig. (2-tailed) shows that there is a significant increase in the mean value of adolescent knowledge before and after health education intervention through peer group education. Based on the results, the p value is <0.05, which means that there is an influence of health education through peer group education on increasing teenagers' knowledge about stunting.